2010
DOI: 10.1080/13607861003713273
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service use among Canadian older adults with anxiety disorders and clinically significant anxiety symptoms

Abstract: Findings indicate that anxious older adults are less likely to use mental health services than those who are depressed. While predisposing and enabling factors do not appear to impede service use, the need for help does. Anxious older adults and those they interact with may not be interpreting their anxiety symptoms as warranting services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 61 publications
(84 reference statements)
3
30
1
3
Order By: Relevance
“…These needs were reported both by those who obtained help for their mental health problems, considering that the help that they had received was not enough, and by those who were not able to access the required service, even after they had requested it. The findings also showed that the majority of the help was being provided by the general practitioner, consistent with previous observations (de Beurs et al, 1999;Holvast et al, 2012;Scott, Mackenzie, Chipperfield, & Sareen, 2010).…”
Section: Page 6 Of 16supporting
confidence: 80%
“…These needs were reported both by those who obtained help for their mental health problems, considering that the help that they had received was not enough, and by those who were not able to access the required service, even after they had requested it. The findings also showed that the majority of the help was being provided by the general practitioner, consistent with previous observations (de Beurs et al, 1999;Holvast et al, 2012;Scott, Mackenzie, Chipperfield, & Sareen, 2010).…”
Section: Page 6 Of 16supporting
confidence: 80%
“…Ces résultats sont comparables à ceux observés dans d'autres études (Cairney, Corna et Streiner, 2010 ;Scott et al, 2010) et appuient l'idée que, dans un contexte où les services de santé sont financés par un programme d'assurance public, le statut socioéconomique n'influence pas l'accès aux services.…”
Section: Le Modèle Explicatifunclassified
“…Ces résultats concordent avec ceux d'autres études ayant rapporté une prévalence plus élevée de symptômes de détresse psychologique chez les femmes âgées (Djernes, 2006 ;Gadalla, 2010 ;Mojtabai et Olfson, 2004 ;Wight, Cummings, Karlamangla et Aneshensel, 2009) ainsi qu'une plus grande utilisation des services en santé mentale par celles-ci (Crabb et Hunsley, 2006 ;Han et al, 2011). D'autres études canadiennes n'ont, cependant, pas trouvé d'association directe entre le genre et l'utilisation des services de santé (Cairney et al, 2010 ;Cole, McCusker, Sewitch, Ciampi et Dyachenko, 2008 ;Scott et al, 2010). En ce qui concerne l'effet de l'âge, nos résultats concordent avec ceux d'autres études ayant rapporté une plus grande prévalence de détresse psychologique (Mojtbai et Olfson, 2004) et une plus grande utilisation des services de santé par les personnes moins âgées (Cole et al, 2008 ;Crabb et Hunsley, 2006).…”
Section: Le Modèle Explicatifunclassified
See 1 more Smart Citation
“…Several practical barriers have been identified, including finances (1416). Need (i.e., diagnosis, symptom severity, disability) emerges as another important factor (1720). Unfortunately, older adults with psychiatric disorders are less likely than younger adults to perceive need for care (19, 21); approximately half do not perceive such need (21, 22).…”
mentioning
confidence: 99%